2007
DOI: 10.4049/jimmunol.178.10.6350
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for CD4 T Cell Help in Maintenance of Memory CD8 T Cell Responses Is Epitope Dependent

Abstract: CD4 Th cells play critical roles in stimulating Ab production and in generating primary or maintaining memory CTL. The requirement for CD4 help in generating and maintaining CTL responses has been reported to vary depending on the vector or method used for immunization. In this study, we examined the requirement for CD4 T cell help in generating and maintaining CTL responses to an experimental AIDS vaccine vector based on live recombinant vesicular stomatitis virus (VSV) expressing HIV Env protein. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Importantly, compared with vaccination with BCG/protein and BCG alone, BCG/DNA regimen can induce higher levels of IFN-γ and IL-2 which are characteristics of Th1 response. The majority of researches indicated that Th1 immune response is essential for Mtb growth control [37], and the strong Th1 response induced by BCG is favorable to aid the maturation and maintenance of CTL [38], which strongly amplifies CTL responses. Furthermore, Th1 cells mainly develop after intracellular bacteria and some virus infection [39].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, compared with vaccination with BCG/protein and BCG alone, BCG/DNA regimen can induce higher levels of IFN-γ and IL-2 which are characteristics of Th1 response. The majority of researches indicated that Th1 immune response is essential for Mtb growth control [37], and the strong Th1 response induced by BCG is favorable to aid the maturation and maintenance of CTL [38], which strongly amplifies CTL responses. Furthermore, Th1 cells mainly develop after intracellular bacteria and some virus infection [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, it did induce an antibody response similar to that of the mice infected with wt VSV, most likely due to the systemic spread of virus to peripheral organs, such as the spleen and lymph nodes. Previous studies have shown that wt VSV infection of immunocompetent mice results in the CD4 ϩ T-cell-dependent production of neutralizing IgG antibodies and the induction of a virus-specific cytotoxic T lymphocyte response (9,14,17). Therefore, given the similarity in the antibody responses induced by the rwt and rM51R-M viruses, it is likely that rM51R-M virus induces T-cell and memory responses comparable to those observed with wt VSV strains.…”
mentioning
confidence: 96%
“…We then investigated CD8 þ T-cell responses vs the tumor (AH1 endogenous MuLV gp70 epitope expressed in CT26 N-SPSYVYHQF-C) 26 and the OV (nucleocapsid epitope N-MPYLIDFGL-C) 27 9 days post-infection. At this time-point, we saw that inclusion of the opt.hIL-15 transgene greatly enhanced anti-tumoral immunity (Figure 4c; Po0.05; Student's t-test), while not modifying the immune response vs the vector (Figure 4d).…”
Section: Il-15 Transgene Enhances Oncolytic Vsvmentioning
confidence: 99%